Angiotensin II modulates VEGF-driven angiogenesis by opposing effects of type 1 and type 2 receptor stimulation in the microvascular endothelium - Carbajo-Lozoya, Javier; Lutz, Susanne; Feng, Yuxi; Kroll, Jens; Hammes, Hans-Peter; Wieland, Thomas (Cellular signalling, 2012)
Vascular endothelial growth factor (VEGF) is a main stimulator of pathological vessel formation. Nevertheless, increasing evidence suggests that Angiotensin II (Ang II) can play an augmentory role in this process. We thus analyzed the contribution of the two Ang II receptor types, AT1R and AT2R, in a mouse model of VEGF-driven angiogenesis, i.e. oxygen-induced proliferative retinopathy. Application of the AT1R antagonist telmisartan but not the AT2R antagonist PD123,319 largely attenuated the pathological response. A direct effect of Ang II on endothelial cells (EC) was analyzed by assessing angiogenic responses in primary bovine retinal and immortalized rat microvascular EC. Selective stimulation of the AT1R by Ang II in the presence of PD123,319 revealed a pro-angiogenic activity which further increased VEGF-driven EC sprouting and migration. In contrast, selective stimulation of the AT2R by either CGP42112A or Ang II in the presence of telmisartan inhibited the VEGF-driven angiogenic response. Using specific inhibitors (pertussis toxin, RGS proteins, kinase inhibitors) we identified G12/13 and Gi dependent signaling pathways as the mediators of the AT1R-induced angiogenesis and the AT2R-induced inhibition, respectively. As AT1R and AT2R stimulation displays opposing effects on the activity of the monomeric GTPase RhoA and pro-angiogenic responses to Ang II and VEGF requires activation of Rho-dependent kinase (ROCK), we conclude that the opposing effects of the Ang II receptors on VEGF-driven angiogenesis converge on the regulation of activity of RhoA-ROCK-dependent EC migration.